Studi Perencanaan Pemasangan Genset Emergency Pada Gedung C Fakultas Teknik Universitas Riau - Septianto, Dekri; Firdaus, Firdaus; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru often get a power outage from PLN. It is make disruption of activities and learning process at building C of the Faculty of Engineering University of Riau. At building C of the Faculty of Engineering University of Riau supply of electricity from PLN and genset. Genset installed in the building currently only supplies the third floor of the building. So if the energy supply of PLN is dead then the second floor and the first floor does not get supply of electrical power from the genset.This study discussed about the needs and usage scheme automatically loads. Analysis of load usage based on need. Results of analysis are used to determine the priority use of the power generator. From the simulation results ETAP 12.6 are that the emergency power requirement of first priority is 12.8 A, second priority is 1.7 A, third priority is 1.5 A, fourth priority is 1.7 A, fifth priority is 1.7 A, sixth priority is 1.9 A, seventh priority is 1.9 A, eighth priority is 5.6 A. The user schema automatically load was simulated using Proteus 8 professional.Keyword: automatic load usage scheme.